Tourism communication and local wisdom of the baduy tribe - Eka Susilawati; Shulbi Muthi Sabila Salayan Putri; Ganjar Kurniawan Ramdani; Noerma Kurnia Fajarwati; Rizqi Fitrianti; Neni Yulianita (The International Journal of Politics and Sociology Research, 2023)
Baduy is one of the typical tribes in Indonesia. This study aims to examine changes in the communication of visitors and native Baduy in maintaining the local wisdom of typical indigenous tribes. This study uses a qualitative method. Data collection techniques were carried out through literature studies. Data analysis techniques use data collection, data reduction, data presentation, and data verification or drawing conclusions. The results of this study indicate that the cultural elements of the Baduy tribe in the midst of global developments are starting to change. It is important to involve stakeholders so that communication must be directed at each party so that all can play a role, accompany the development of regional potential, support the region both from an economic, cultural and educational point of view.